Solubility Enhancement of Clozapine Through Co-Crystal Formation with Isonicotinamide - Fikri Alatas; Hestiary Ratih; Hesti Kurnia; Sundani Nurono Soewandhi (Universitas Padjadjaran (Unpad), 2020)
Clozapine (CLO) is an effective atypical antipsychotic to control the symptoms of psychosis and schizophrenia. Clozapine has low solubility and high permeability, so it is classified as a class II in the biopharmaceutical classification system. The aim of this study was to improve the solubility and dissolution rate of clozapine by clozapine-isonicotinamide (CLO-INA) co-crystal formation. CLO-INA co-crystal was prepared by solvent-drop grinding (SDG) method using water as a solvent. Characterization of SDG result was conducted by powder X-ray diffraction (PXRD) and Fourier transform infrared (FTIR). Solubility test was performed in water at room temperature. The dissolution test was performed in 900 mL of pH 6.8 phosphate buffer solution, 50 rotation per minute of paddle rotation, and at 37±0.5 °C. The PXRD pattern of SDG result of CLO-INA has many different peaks from its parent components, and this may indicate the co-crystal formation. The solubility of the co-crystal clozapine was fifteen folds higher than pure clozapine. The dissolution rate of CLO-INA co-crystal increased in the first 10 minutes compared to pure clozapine. Percentage of clozapine dissolved after 10 minutes from CLO-INA co-crystal and pure CLO were 10.2 and 2.4%, respectively. CLO and INA can form co-crystal by SDG method that can improve the solubility and dissolution rate of clozapine.Keywords: Clozapine, Isonicotinamide, Co-crystal, Solubility, Dissolution